Elevated blood basophil count may has a role in etiopathogenesis of isolated coronary artery ectasia - Yilmaz, Mucahid; Kayancicek, Hidayet; Gozel, Nevzat; Cekici, Yusuf; Bilen, Mehmet Nail; Sarıoğlu, Güney; Korkmaz, Hasan H. (My University, 2019)
The pathophysiology of isolated coronary artery ectasia (CAE) takes in inflammation and atherosclerosis. It is clear that basophils have a critical role in endothelial dysfunction, atherosclerosis and inflammation. In this study, it was aimed to examine the association between isolated CAE and basophilia. All cases who underwent coronary angiography between January 2013 and April 2018 evaluated retrospectively. Of 10985 cases, 173 (107 males) with isolated CAE and 220 with normal coronary angiography (NCA) that age and gender matched subjects (119 males) were recorded. Hospital’s database was used to derive the biochemical and hematological test results, and baseline characteristics. White blood cell (WBC) count and basophil count were significantly elevated for the cases that have angiographic isolated CAE when compared to the subjects with NCA [ 7.87 (6.83-9.42)109/ L vs 7.48 (6.27-8.67) 109/ L, p=0.01; 0.04 (0.03-0.05) 109/ L vs 0.03 (0.02-0.05) 109/ L, p=0.03, respectively]. According to receiver operating characteristics curve analyses (ROC); the specificity of a basophil value > 0.037 109/ L (measured prior to coronary angiography) in predicting isolated CAE was 57,3% and the sensitivity was 57.2% (area under the curve [AUC] 0.562, 95% CI 0.505, 0.618; p=0.03). Patients with isolated CAE have higher blood basophil count. Elevated blood basophil count may have a substantial mission in the pathogenesis of isolated CAE.
Keywords: Biyoloji; Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp; Kalp ve Kalp Damar Sistemi